HEPATIC ENCEPHALOPATHY IN CHRONIC LIVER DISEASE PRODUCED BY CHRONIC VIRAL HEPATITIS - Nazir, Aamir; Taimoor, Alruba; Munazza, Bibi; Qureshi, Sadaf Anwar (Pakistan Journal of Physiology, 2017)
Background: Hepatic encephalopathy (HE) involves neuropsychiatric dysfunction as a result of metabolic disturbance. The objective of the study was to determine and compare grades of hepatic encephalopathy in patients of viral hepatitis B, C, and co-infection. Methods: A cross-sectional study was designed which included seventy five patients of chronic HBV, HCV, and co-infection of either sex, aged 35 years or above. The patients were equally divided into 3 groups. Hepatic encephalopathy was classified into four grades based on the West Haven classification. Results: Out of the 75 subjects, 51 (68.0%) were males and 24 (32.0%) were females. The Mean age was 44.69Â±7.423 years. Grade I hepatic encephalopathy was a significant feature of both chronic HCV and co-infection groups. The development of grade II encephalopathy was more marked in chronic HBV group, while grade III encephalopathy was more frequent in chronic HCV group. However, frequency distribution of grade IV encephalopathy remained same in all groups. Conclusion: The study concluded that progression of encephalopathy was not more marked in co-infection group. In fact, hepatic encephalopathy equally developed in study groups. Keywords: Chronic liver disease, Hepatic encephalopathy, viral hepatitis Pak J Physiol 2017;13(2):38â€“40